1983
DOI: 10.1042/bj2110191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hyaluronate in differentiated teratocarcinoma cells. Mechanism of chain growth

Abstract: Hyaluronate could be labelled in vivo with [32P]phosphate. [32P]UDP in an alpha-glycosidic linkage constituted the reducing end of membrane-bound hyaluronate. The UDP is liberated during further chain elongation, indicating that chain growth occurs at the reducing end. [3H]Uridine could be incorporated into hyaluronate during synthesis on the isolated membraneous fraction from [3H]UDP-GlcNAc and [3H]UDP-GlcA, confirming the identification of UDP as a constituent of membrane-bound hyaluronate. These results led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 48 publications
5
72
2
2
Order By: Relevance
“…Subsequent work by this laboratory on the Group A streptococcal HAS enzyme gave corroborating data (11). On the other hand, two other groups concluded that HA was extended by the addition of sugars to the reducing end in experiments with native mammalian HAS preparations (12)(13)(14). It is obvious that direct experiments with defined systems utilizing purified enzyme will be necessary to address these issues.…”
Section: Table I Acceptor Use Of Various Recombinant Ha Synthasesmentioning
confidence: 58%
See 1 more Smart Citation
“…Subsequent work by this laboratory on the Group A streptococcal HAS enzyme gave corroborating data (11). On the other hand, two other groups concluded that HA was extended by the addition of sugars to the reducing end in experiments with native mammalian HAS preparations (12)(13)(14). It is obvious that direct experiments with defined systems utilizing purified enzyme will be necessary to address these issues.…”
Section: Table I Acceptor Use Of Various Recombinant Ha Synthasesmentioning
confidence: 58%
“…In comparing these various studies, the analysis of the enzymatically released sugars from the streptococcal system added more rigorous support for their interpretation (11). In another type of experiment, HA made in mammalian cells was reported to have a covalently attached UDP group as measured by an incorporation of low amounts of radioactivity derived from 32 P-labeled UDP-sugar into an anionic polymer (14). These data implied that the last sugar was transferred to the reducing end of the polymer.…”
mentioning
confidence: 99%
“…of assembled HA-UDP chains and how HA·HAS complexes can stay together for hours, without dissociating, during a processive synthetic process that occurs at the reducing end (Prehm 1983;Bodevin-Authelet et al 2005;Tlapak-Simmons et al 2005). Many RNA and DNA enzymes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For the Class I HASs this UDP will arise from the last sugar unit added, whereas for the Class II pmHAS this UDP will be from the first sugar used to initiate the HA chain. Evidence for the covalent attachment of UDP to HA was reported for the Class I HASs (33), but this has not yet been assessed for the pmHAS. Of course, because a HA-UDP linkage is much less stable under physiological conditions than either type of glycoside bond in HA, it will likely be cleaved and, therefore, UDP will be absent in "mature" HA or commercial HA preparations that have been processed in various ways.…”
Section: Mechanism Of Ha Biosynthesis By the Class I Streptococcal Hamentioning
confidence: 99%
“…The direction of synthesis for the Class I streptococcal HASs has not yet been reported. Earlier studies using crude membrane preparations from eukaryotic cells (33,34) suggested that HA synthesis occurs at the reducing end, in which case the growing HA chain would always be attached to UDP (35). However, some of these earlier results might have alternative interpretations, since the systems used were not pure and other glycosyltransferase activities were present.…”
Section: Mechanism Of Ha Biosynthesis By the Class I Streptococcal Hamentioning
confidence: 99%